PENGARUH PENGGUNAAN VARIASI KONSENTRASI AVICEL PH-101 PADA FORMULA TABLET PREDNISOLONE - hilda suherman (Universitas Harapan Bangsa Purwokerto, 2017)
Abstract Prednisolone is a steroid class drug that is used to treat certain types of allergies, inflammatory conditions, autoimmune disorders and cancer. Solubility of prednisolone is very difficult to dissolve in water causing problems in the absorption process so that the optimum formula is needed to form Prednisolone tablets that meet the requirements of the physical properties of tablets. The purpose of this study was to make the optimum formula with a combination of lactose excipients, avicel pH-101, and amprotab to obtain prednisolone tablets with good physical properties and dissolution. Prednisolone tablets made 7 formulas with a combination of lactose (A) Avicel PH-101 (B), and Amprotab (C), Formula I (100% A); Formula II (100% B); Formula III (100% C); Formula IV (50% A + 50% B); Formula V (50% A + 50% C); Formula VI (50% B + 50% C); Formula VII (33.33% A + 33.33% B + 33.33% C) in 2 batches. The method of making prednisolone tablets by direct printing. Testing of prednisolone tablets included the physical properties of tablets, weight uniformity, uniformity in size, hardness, friability, disintegration time, and dissolution test, and content determination. Keywords: optimization of formulas, tablets, Prednisolone, Simplex Lattice Design.